Kingdon’s multiple streams framework: what happens next? - Paul Cairney (International Review of Public Policy)
The multiple streams framework (MSF) has much to offer new and experienced scholars. Kingdon’s agenda setting book on US policymaking inspired one of the most applied theories in international policy research. Compared to other theories, this activity emerged in the relative absence of central direction. In this context, I argue that instilling MSF direction and rigour will appeal to a small core group but not to a large periphery. If most MSF applications are by scholars who have only bought Kingdon’s work so far, how can we sell them the entire state-of-the-art MSF package?